Perspektif Historis: Kontinuitas dan Perubahan Peran Perpustakaan Islam - Lutfi Azzahrowaini; Mutohharun Jinan (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2025)
Abstract: This study explores the strategic role of Islamic libraries in shaping civilization, emphasizing their historical foundations, contributions of major libraries, and the challenges of preserving manuscripts in the modern era. The study employs a qualitative descriptive-analytical approach, focusing on historical literature reviews and thematic analysis to uncover the functions and roles of Islamic libraries throughout different historical periods. The findings highlight that Islamic libraries, such as Bayt al-Hikmah in Baghdad, Dar al-Hikmah in Cairo, and the libraries of Cordoba, were not merely repositories of manuscripts but pivotal centers for education, research, cultural preservation, and knowledge distribution. These institutions facilitated the translation and dissemination of works from Greek, Persian, and Indian traditions, significantly influencing both Islamic and Western intellectual developments. Despite their historical contributions, Islamic libraries faced challenges, including the destruction during the Mongol invasion of Baghdad in 1258 CE and the Reconquista in Andalusia in 1492 CE, which resulted in the loss of invaluable manuscripts. In the modern era, issues such as manuscript deterioration and inadequate preservation facilities persist, highlighting the need for digitization and global collaboration. This study underscores the imperative to safeguard the intellectual legacy of Islamic civilization for future generations.